Державне управління фрілансовою діяльністю в умовах розвитку національного ринку - Солярчук, Наталія Юріївна (Національний університет "Львівська політехніка", 2015)
У дисертаційній роботі вирішено наукове завдання з розроблення теоретичних основ та практичних рекомендацій щодо удосконалення державного управління фрілансовою діяльністю в умовах розвитку національного ринку. Після детального опрацювання літературних джерел уточнено понятійний та термінологічний апарат щодо фрілансової діяльності, удосконалено класифікацію фрілансерів з урахуванням їх особливостей, модель процесу виконання фріланс-проекту. Вперше запропоновано систему показників оцінювання стану фрілансової діяльності на рівні держави. Проаналізовано рівень доходів фрілансерів, виявлено тенденції зміни частки фрілансерів у складі економічно-активного населення, проаналізовано результати соціологічного дослідження щодо стану фрілансової діяльності в Україні, проведеного автором. Удосконалено систему державного управління фрілансовою діяльністю. В диссертационной работе решена научная задача по разработке теоретических основ и практических рекомендаций по совершенствованию государственного управления фрилансовой деятельностью в условиях развития национального рынка. После детальной проработки литературных источников уточнен понятийный и терминологический аппарат относительно фрилансовой деятельности, усовершенствована классификация фрилансеров с учетом их особенностей, модель процесса выполнения фриланс-проекта. Впервые предложена система показателей оценки состояния фрилансовои деятельности на уровне государства. Проанализирован уровень доходов фрилансеров, выявлены тенденции изменения доли фрилансеров в составе экономически активного населения, проанализированы результаты социологического исследования о состоянии фрилансовой деятельности в Украине, проведенного автором. Усовершенствована система государственного управления фрилансовой деятельностью. In the dissertation work there is solved the scientific problem of development of theoretical foundations and practical recommendations for improvements in state administration of freelance activity in terms of national market development. The object of the research is the process of freelance activity state administration. The subject of the research is referred to the theoretical and practical principles of state administration of freelance activity in terms of national market development. In the first chapter «The theory and practice of state administration of freelance activity» there are determined the essence and importance of freelance activity, represented a list of freelance activity advantages and disadvantages, improved a model of freelance project implementation, which determines the basic stages of simple and complex project with specification of responsibles for each stage, in order to provide the qualified organization of freelance projects management process. After careful studding of literary sources the concepts and terminology for freelance activity, took farther development, including such terms as: freelancer - a qualified worker who isn’t in the staff and is independently engaged in business activities, collaborates with the customer only for a period of working over the freelance project, doesn’t hire employees; freelance activity - is the kind of entrepreneurial activity, which is carried out by qualified freelance workers without involving hired labor mainly in the distant form with the aim of getting profit and achieving the goals; freelance project - an activity of one or more freelancers, which is limited by terms and costs for implementation of unique work for a specific customer with the aim of getting profit and other goals; state administration of freelance activity - is the performance of the administrative influence of public authorities on the implementation of freelance activity for ensuring the development of the national economy through the increasing of freelance activity efficiency and legalization. A clear definition of these concepts will allow to prevent the identification of remote freelance work with other related notions, to distinguish the freelancers among entrepreneurs. Also there is represented the classification of freelancers by the following classification criterias: by the method of communication, by the type of employment; by aworkplace; by the reason for choosing freelancing as a basic type of activity, by the structure of the market, by the methods of finding new customers. There are determined the basic principles of freelance activity state administration: the principle of purpose, the principle of planning, the principle of competence, the principle of the interests and needs consideration, the principle of efficiency, the principle of continuous improvement management tools. The functions of the freelance activity state administration including planning, organizing, promotion, control and regulation are proposed. In the second chapter «The analysis of freelance activity as a form of entrepreneurship» there are formed the methodical aspects of freelance activity analysis, with the use of sociological freelancers survey conducted by the author, there is determined the influence of freelance activity on the level of employment and migration. To assess the state of freelance activity there was carried out the sociological research, that was driven remotely using an Internet resource Google Docs and provided an opportunity to identify the trends of freelance activity, the advantages and disadvantages of its implementation in a transitional economy of Ukraine. The results of the study and research of statistical data of freelance online job boards indicate further growth in the number of freelancers that proves the need of improvements in the legislative base and government support for freelance activity. In the third chapter «Improving of state administration of freelance activity» there are proposed the state administration instruments of freelance activity, the state administration system of freelance activity, proved the program of the freelance activity development in Ukraine, accomplished evaluation of freelance activity development potential. Activity of freelancers in Ukraine can be partly attributed to the informal economy, as far as freelance activity, being a part of the informal economy, is hidden from official statistics. It is necessary to create favorable conditions for the development of freelance activity and its legalization in Ukraine. To the tools of freelance activity state administration we propose to include: improvement of the freelance activity legal base, stimulating tax policy within freelance activity and tax benefits for freelancers, provision of dedicated funding for the freelancer’s professional skills improvement and their retraining, development and implementation of a mechanism that confirm the freelancers informal professional training and publication of relevant certificates, the formation of the mechanism of government contracts for freelance services and attraction of freelancers to work on government projects and programs, creating conditions and regulatory cooperation with international and national online job boards for freelancers, providing social guarantees for freelancers and so on. Particularly in the research were proposed zero tax rates for freelancers during their studying, retraining or qualification improvement and in case of a lower level of income comparing to freelance minimum wage. There are determined the basic prerequisites for the formation of freelance activity development program, the main tasks for certain public authorities, the implementation of which is necessary for provision of the most effective freelance activity development. We propose to distribute these tasks among public authorities such as the State Service for Regulatory Policy and Entrepreneurship Development and State Employment Office of Ukraine. There is proposed the system of indicators for the evaluation of state freelance activity that covers the freelancers proportion in the total number of the economically active population, the proportion of the contribution of freelancers residents in gross domestic product, gross national product, the level of legalization of freelance activity. These indicators enable the government to monitor the freelancers number, their dynamics - to evaluate the development of freelance activity as well as state and the role of freelance activity in the development of national economy of Ukraine.
Государственное управление фрилансовой деятельностью в условиях развития национального рынка
State administration of freelance activity in terms of national market development
Keywords: фрілансер; фрілансова діяльність; державне управління фрілансовою діяльністю; фріланс-проект; інтернет-біржа фрілансу; система державного управління фрілансовою діяльністю; показники оцінювання стану фрілансової діяльності; фрилансер; фрилансовая деятельность; государственное управление фрилансовой деятельностью; фриланс; интернет-биржа фриланса; система государственного управления фрилансовой деятельностью; показатели оценки состояния фрилансовои деятельности; freelancer; freelance activity; state administration of freelance activity; freelance project; freelance online job board; the system of freelance activity state administration; indicators of freelance activity status evaluating